Math

I don't understand how log2 √(1/2) turned into log2 2^(-1/2).

Quote:
You will have to know the 3 prime properties of logs

1. logk (AB) = logk A + logk B
2. logk(A/B) = logk A - logk B
3. logk (A^n) = n logk A
where k is any positive number , k ≠ 1

so log2√36 - log2 log2</sub√72
= log2 (√36/√72)
= log2 √(36/72)
= log2 √(1/2)
= log2 2^(-1/2)
= (-1/2) log2 2
= (-1/2)(1)
= -1/2

1. 👍 0
2. 👎 0
3. 👁 63
1. It would be so much easier if we could identify you by some name other than Anonymous.

1. 👍 0
2. 👎 0
posted by Reiny

Similar Questions

1. Math

I don't understand how log2 √(1/2) turned into log2 2^(-1/2). Quote: You will have to know the 3 prime properties of logs 1. logk (AB) = logk A + logk B 2. logk(A/B) = logk A - logk B 3. logk (A^n) = n logk A where k is any

asked by Anonymous on June 24, 2015
2. Math

I don't understand how log2 √(1/2) turned into log2 2^(-1/2). Quote: You will have to know the 3 prime properties of logs 1. logk (AB) = logk A + logk B 2. logk(A/B) = logk A - logk B 3. logk (A^n) = n logk A where k is any

asked by Anonymous on June 24, 2015
3. Urgent math

i need help with these two homework problems Use the Laws of Logarithms to combine the expression into a single logarithm log2 5 − 5 log2 x + 1/2 log2(x + 1) Solve the logarithmic equation for x log2(x + 2) + log2(x − 1) = 2

asked by Emma on August 3, 2015
4. Math

Hello! Could someone please take a look at the problem below and let me know if I made mistakes in simplifying the given equation? I'm quite certain that I did make a mistake somewhere because the original equation and its

asked by Constantine on May 31, 2015
5. Logarithms

I'm working on logarithmic equations and I'm stuck on how my book arrives at the next step. First, they use the change of base formula on, log(sqrt(2))(x^3 - 2) (sqrt(2)) is the base,changing to base 2 log(sqrt(2))(x^3 - 2)=

asked by Helper on March 9, 2011
6. math

solve the equation log2(x+4)-log4x=2 the 2 and 4 are lower than the g This is what I got: log2(x+4)+log2(4^x)=2 log2((x+4)*4^x)=2 4^x(x+4)=4 x=0 is a solution???

asked by anonymous on January 9, 2013
7. math30

1.Use the laws of logarithms to express log2 (6) â€“ log2 (3) + 2log2 (8)^1/2 as a single logarithm; then evaluate. 2. For logy = log(0.5x â€“ 3) + log2, express y as a function of x.

asked by alejandro on July 10, 2012
8. Math - Logarithmic

Solve: 2^(5x-6) = 7 My work: log^(5x-6) = log7 5x - 6(log2) = log7 5x = log7 + 6(log2) x = (log7 + log2^6) / 5 And textbook answer: (log7) / (log2) What did I do wrong?

asked by Anonymous on December 13, 2007